1963
DOI: 10.1111/j.1744-7348.1963.tb03756.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature on the emergence of the cabbage root fly (Erioischia brassicae (Bouché)) from overwintering pupae

Abstract: SUMMARYThe pupae of Erioischia brassicae (Bouché) overwinter in diapause, which extends for 105–126 days at a constant temperature of 41° F. (5° C.) and terminates, in the field, between the end of January and the beginning of February. Morphogenesis is completed at constant temperature after an accumulation of about 368 day degrees above 42° F., and in the field at Wellesbourne the first flies usually emerge during April.Phenological relationships of emergence and beginning of oviposition with accumulated day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
1

Year Published

1973
1973
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 5 publications
2
32
1
1
Order By: Relevance
“…The estimated time to complete diapause in our pupae was slightly longer than reported previously (Coaker & Wright, 1963;Missonier, 1963), due partly to the use of the 50 and 90% emergence levels as criteria for termination of diapause. Despite this, in every case, diapause development was complete while less than 1 D" > 6", was accumulated in the soil every 2 days (Fig.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The estimated time to complete diapause in our pupae was slightly longer than reported previously (Coaker & Wright, 1963;Missonier, 1963), due partly to the use of the 50 and 90% emergence levels as criteria for termination of diapause. Despite this, in every case, diapause development was complete while less than 1 D" > 6", was accumulated in the soil every 2 days (Fig.…”
Section: Discussioncontrasting
confidence: 46%
“…Despite this, in every case, diapause development was complete while less than 1 D" > 6", was accumulated in the soil every 2 days (Fig. This suggests that it may be feasible to begin spring D" accumulation from the day when, for example, the rate of D" accumulation increases to 1 Do/day, rather than from an arbitrarily chosen fixed date (Coaker & Wright, 1963;Finch, 1977). This suggests that it may be feasible to begin spring D" accumulation from the day when, for example, the rate of D" accumulation increases to 1 Do/day, rather than from an arbitrarily chosen fixed date (Coaker & Wright, 1963;Finch, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4; Table 3), which was similar to observations of other researchers (Nair andMcEwan 1975, Collier and. Coaker and Wright (1963) suggested that the magnitude of the time lag between emergence and ßight may depend on spring temperature and precipitation regimens, with cool, wet weather delaying ßight, which Þts with our observations. In 2002 and 2003, there was substantially more rainfall between emergence and ßight than in 2001 and 2004 (Fig.…”
Section: Spring Flight Activitysupporting
confidence: 86%
“…It could be due to a change in the adult sex ratio in favour of the male, or to emigration. A further possible cause is variation in the availability of carbohydrate food to the female, since this is essential for oviposition (Coaker & Wright 1963;Finch & Coaker 1969;Finch 1971). If ko is in fact due to an inadequate food supply, it may be possible to manipulate English populations by interference with the food supply by cultural or chemical means (see Finch & Skinner 1971).…”
Section: Discussionmentioning
confidence: 98%